PENINGKATAN HASIL BELAJAR PESERTA DIDIK DALAM MENCIPTAKAN TARI KREASI MENGGUNAKAN MODEL PROJECT BASED LEARNING DI KELAS V SDN 10 PASAR MUARA LABUH KABUPATEN SOLOK SELATAN - Intan Dwi Puspita; Desyandri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low learning outcomes of students in creating dance. The purpose of this research is to describe the improvement of student learning outcomes in creating creative dance using the Project Based Learning (PjBL) model in Class V at SDN 10 Pasar Muara Labuh, Solok Selatan Regency. This research uses Classroom Action Research (CAR) with two approaches: qualitative and quantitative. This study was conducted in two cycles, with the research procedure consisting of planning, implementation, observation, and reflection. Data collection techniques include observation analysis, interviews, tests, and non-tests. The subjects of this research are the class teacher as observer, the researcher as practitioner, and 12 fifth-grade students. The results showed an increase: first, the teaching module in Cycle I obtained an average of 83.2%, which increased in Cycle II to 95.8%. Second, the teacher aspect in Cycle I obtained an average of 84.75%, increasing in Cycle II to 93.7%. Third, the student aspect in Cycle I obtained an average of 82.68%, increasing in Cycle II to 93.7%. Fourth, student learning outcomes in Cycle I obtained an average score of 68.5, increasing in Cycle II to 80. Thus, it can be concluded that the Project Based Learning (PjBL) model can improve student learning outcomes in dance education in Class V at SDN 10 Pasar Muara Labuh.